Regenerated cellulose fiber quilt core material and preparation method thereof
By using hollow coaxial spinning technology and asymmetric cooling method of regenerated cellulose fibers, polylactic fibers and erine fibers in the core material, an asymmetric curling structure is formed, which solves the problems of reduced fluffiness and uneven fiber dispersion during use of the existing core material, and achieves better warming performance and durability.
Patent Information
- Application Number
- CN202510407090.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-04-29
AI Technical Summary
During use, existing cored materials will cause fiber aging and fluffiness due to human pressure, and the filling fibers are prone to displacement, clumps and hollows, resulting in uneven warming performance.
A mixture of regenerated cellulose fibers and polylactic acid fibers was used to perform hollow coaxial spinning with serole fiber solution, and the fibers were cooled by asymmetric cooling method to form an asymmetric crimp structure. Combined with carding, web laying and shaping treatment, a cored material with improved fluffy and mechanical strength was prepared.
By combining the elasticity and restorability of the regenerated cellulose fibers with the hardness and mechanical strength of the syrup fibers, the problems of insufficient fluffiness and uneven fiber dispersion after being used for too long are solved, and the overall uniformity and durability of the core material are improved.
Smart Images

Figure CN119900130A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quilt core material preparation, in particular to a regenerated cellulose fiber quilt core material and a preparation method thereof. Background Art
[0002] Quilt core material is a bedding product mainly used for warmth, which is made of quilt cover and filling material sewn in an appropriate way. As consumers pay more attention to the quality and sustainability of textiles, the quilt core material industry is also constantly innovating technology and developing green. There are many types of quilt core material products, including down quilts, wool quilts, cotton quilts, chemical fiber quilts, etc. The design concept of the products has also gradually evolved from simple warmth to comfort.
[0003] The core material will be subjected to human pressure during use, especially when the weight of the human body acts on a certain area of the core material for a long time, which will cause the fibers of the core material to be compressed. As time goes by, the fibers of the core material will age and lose their original fluffiness. If the fibers filled in the core material are sparse or contain a large number of short fibers, they are prone to shifting during use, resulting in defects such as fiber clumps and voids, making the thermal insulation performance uneven.
[0004] Therefore, it is necessary to improve the preparation method of the quilt core material in the prior art to solve the above problems. Summary of the invention
[0005] The present invention overcomes the shortcomings of the prior art and provides a regenerated cellulose fiber quilt core material and a preparation method thereof, aiming to solve the problems of insufficient fluffiness and uneven fiber dispersion caused by long-term use of the quilt core material in the prior art.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a regenerated cellulose fiber quilt core material, comprising the following steps: S1: dissolving regenerated cellulose fiber and polylactic acid fiber to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution; S2: dissolving kenaf fibers to obtain a kenaf fiber solution, and hollow coaxially spinning the regenerated cellulose fiber / polylactic acid fiber mixed solution in S1 and the kenaf fiber solution to obtain hollow coaxial spun fibers; S3: Cooling the hollow coaxial spun fiber in S2 by an asymmetric cooling method to obtain a cooled hollow coaxial spun fiber; S4: combing, web laying and shaping the cooled hollow coaxial spun fibers in S3 to obtain a regenerated cellulose fiber quilt core material.
[0007] In a preferred embodiment of the present invention, the mass ratio between the regenerated cellulose fiber and the polylactic acid fiber in S1 is 6:4-8:2, the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15-20%, and the regenerated cellulose fiber is one of lyocell fiber, viscose fiber and modal fiber.
[0008] In a preferred embodiment of the present invention, the kenaf fiber in S2 is pre-treated by steam explosion, and the steam explosion treatment process is: soaking the kenaf fiber in a 2-5% sodium hydroxide solution for 10-20 minutes, taking out and drying, and then placing the kenaf fiber in a steam explosion device for steam explosion treatment, the air pressure in the steam explosion device is 2-2.5MPa, the steam explosion temperature is 60-80°C, and the pressure holding time is 6-10min.
[0009] In a preferred embodiment of the present invention, the kenaf fiber dissolution process in S2 is to place the kenaf fiber in a vacuum drying oven at 70°C and dry it for 12 hours, then immerse the dried kenaf fiber in an ionic liquid and stir it at a stirring speed of 500-700rpm for 2-3 hours, and the concentration of the obtained kenaf fiber solution is 10-15%.
[0010] In a preferred embodiment of the present invention, the mass ratio of the regenerated cellulose fiber / polylactic acid fiber mixed solution and the kenaf fiber solution in S2 is 5:5-7:3, and the spinning method used in the hollow coaxial spinning is coaxial electrospinning.
[0011] In a preferred embodiment of the present invention, the process of hollow coaxial spinning in S2 is: the hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixed solution is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed, and the spinning voltage is 15-20kV.
[0012] In a preferred embodiment of the present invention, the cross-section of the spinning outlet in S2 is one of a triangle and an ellipse.
[0013] In a preferred embodiment of the present invention, the asymmetric cooling method described in S3 is to cool the hollow coaxial spinning fiber by blowing air on both sides, with a cooling temperature of 5-10°C and a wind speed of 10-20m / s on one side and a cooling temperature of 25-30°C and a wind speed of 3-5m / s on the other side.
[0014] In a preferred embodiment of the present invention, the combing speed in S4 is 10-30 m / min, the setting temperature is 120-150° C., and the setting time is 5-10 min.
[0015] In order to achieve the above-mentioned purpose, the second set of technical solutions adopted by the present invention is: a regenerated cellulose fiber quilt core material, which is prepared based on a regenerated cellulose fiber quilt core material and a preparation method thereof.
[0016] The present invention solves the defects existing in the background technology and has the following beneficial effects: (1) The present invention provides a method for preparing a regenerated cellulose fiber quilt core material, comprising the steps of hollow coaxially spinning a regenerated cellulose fiber / polylactic acid fiber mixture and a kenaf fiber solution, and cooling the spun fibers using an asymmetric cooling method, so that the obtained hollow coaxial fibers produce asymmetric curling. Compared with the quilt core material preparation method in the prior art, the elasticity and recovery of the regenerated cellulose fiber and the polylactic acid fiber are combined with the hardness and mechanical strength of the kenaf fiber, so that the elasticity of the quilt core material can ensure the fluffiness and mechanical strength and avoid lumps and voids caused by uneven fiber dispersion, thereby solving the problems of insufficient fluffiness and uneven distribution of fillers in the quilt core material caused by long-term use of the quilt core material in the prior art.
[0017] (2) In the present invention, the kenaf fiber is pretreated by steam explosion. The steam explosion treatment process is as follows: the kenaf fiber is soaked in a sodium hydroxide solution, taken out and dried, and then placed in a steam explosion device for steam explosion treatment. The content of cellulose and lignin in the kenaf fiber gradually increases, and the content of hemicellulose, pectin and other substances gradually decreases. The crystallinity, degree of polymerization and breaking strength of the kenaf fiber show an upward trend. Compared with the prior art, it helps to improve the fluffiness of the fiber and enable it to maintain a better spatial structure in the quilt core material.
[0018] (3) In the present invention, the hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixed solution is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. Compared with the prior art, the mixture of regenerated cellulose fiber and polylactic acid fiber provides elasticity and recovery, while the addition of kenaf fiber provides additional hardness and mechanical strength, which helps to maintain the fluffiness and shape of the quilt core material and reduce deformation during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 It is a method step diagram of a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0022] like Figure 1 As shown, a method for preparing a regenerated cellulose fiber quilt core material comprises the following steps: S1: dissolving regenerated cellulose fiber and polylactic acid fiber to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution; S2: dissolving kenaf fibers to obtain a kenaf fiber solution, and hollow coaxially spinning the regenerated cellulose fiber / polylactic acid fiber mixed solution in S1 and the kenaf fiber solution to obtain hollow coaxial spun fibers; S3: Cooling the hollow coaxial spun fiber in S2 by an asymmetric cooling method to obtain a cooled hollow coaxial spun fiber; S4: combing, web laying and shaping the cooled hollow coaxial spun fibers in S3 to obtain a regenerated cellulose fiber quilt core material.
[0023] The regenerated cellulose fiber / polylactic acid fiber mixed solution and the kenaf fiber solution are hollow coaxially spun, and the spun fibers are cooled using an asymmetric cooling method, so that the obtained hollow coaxial fibers produce asymmetric curling. The elasticity and recovery of the regenerated cellulose fiber and the polylactic acid fiber are combined with the hardness and mechanical strength of the kenaf fiber, so that the elasticity of the quilt core material can ensure the fluffiness and mechanical strength to avoid lumps and voids caused by uneven fiber dispersion, thereby solving the problems of insufficient fluffiness and uneven distribution of fillers in the quilt core material caused by long-term use of the quilt core material in the prior art.
[0024] The mass ratio between regenerated cellulose fiber and polylactic acid fiber in S1 is 6:4-8:2, the solvent in the regenerated cellulose fiber / polylactic acid fiber mixture is dimethyl sulfoxide, and the total mass concentration of regenerated cellulose fiber and polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixture is 15-20%. At an appropriate mass ratio, the bonding force between regenerated cellulose fiber and polylactic acid fiber is enhanced, which helps to maintain the uniform distribution of fibers during subsequent spinning and post-processing, reduce fiber dispersion and agglomeration, and thus improve the overall uniformity and durability of the quilt core material. The mass ratio of regenerated cellulose fiber and polylactic acid fiber is within this range, which can ensure that the fiber mixture has both good elasticity and recovery, and reduce the impact of decreased fluffiness due to fiber fatigue.
[0025] The kenaf fiber in S2 is pretreated by steam explosion. The steam explosion process is as follows: immersing the kenaf fiber in a 2-5% sodium hydroxide solution for 10-20 minutes, taking out and drying, and then placing the kenaf fiber in a steam explosion device for steam explosion treatment. The air pressure in the steam explosion device is 2-2.5 MPa, the steam explosion temperature is 60-80° C., and the pressure holding time is 6-10 minutes.
[0026] Steam explosion pretreatment can increase the separation degree of kenaf fiber. In this process, the macromolecular structure of kenaf fiber does not change, while hemicellulose, lignin, etc. distributed in the outer layer of the fiber are easily degraded under the action of steam explosion. This helps to improve the fluffiness of the fiber and maintain a better spatial structure in the quilt core material. With the increase of steam pressure, the content of cellulose and lignin in kenaf fiber gradually increases, and the content of hemicellulose, pectin and other substances gradually decreases. The crystallinity, degree of polymerization and breaking strength of kenaf fiber show an upward trend. This helps to improve the mechanical strength and durability of the quilt core material. Sodium hydroxide solution treatment can destroy some hydrogen bonds in kenaf fiber and increase the adsorption capacity of cellulose. This helps in the subsequent steam explosion process, water vapor penetrates deeper into the fiber, thereby more effectively destroying the internal structure of cellulose. Sodium hydroxide solution treatment helps the hydrolysis of hemicellulose, which is particularly obvious in the high temperature and high pressure steam explosion process. The degradation of hemicellulose can increase the exposure of cellulose, improve its accessibility, and increase the crystallinity of kenaf fiber.
[0027] The kenaf fiber dissolution process in S2 is to place the kenaf fiber in a vacuum drying oven at 70°C and dry it for 12 hours, then immerse the dried kenaf fiber in an ionic liquid and stir it at a stirring speed of 500-700rpm for 2-3 hours, and the concentration of the obtained kenaf fiber solution is 10-15%.
[0028] Vacuum drying can remove moisture from kenaf fibers, reduce the adhesion between fibers, and make the fibers more evenly dispersed in the subsequent dissolution process. This uniform dispersion helps to form a uniform fiber network in the quilt core material, thereby improving the fluffiness and uniformity of the quilt core material. As a new type of cellulose solvent, ionic liquid can efficiently dissolve kenaf fibers, and the resulting spinning solution has good spinnability. This treatment method can improve the mechanical strength and softness of the fiber, so that the quilt core material maintains a better shape and structure during use, and reduces the decrease in fluffiness caused by fiber fatigue. Ionic liquid treatment can remove some non-cellulose components in kenaf fibers, such as lignin and hemicellulose, thereby improving the purity and chemical stability of the fiber. This helps to improve the durability and compression resistance of the quilt core material, making the quilt core material less likely to deform during use and maintaining a lasting fluffiness.
[0029] The combination of pretreatment and dissolution process makes the outer layer structure of kenaf more dense and uniform, and combined with asymmetric cooling to form a stable hollow porous structure, improving thermal insulation and fluffiness.
[0030] The mass ratio between the regenerated cellulose fiber / PLA fiber mixture and the kenaf fiber solution in S2 is 5:5-7:3, and the spinning method used in the hollow coaxial spinning is the coaxial electrospinning method. By precisely controlling the mass ratio of the regenerated cellulose fiber and the PLA fiber to the kenaf fiber, the bonding force between the fibers can be optimized and the uniformity of the fiber network can be improved. This uniformity helps to form a stable structure in the quilt core material, thereby improving its fluffiness and durability.
[0031] The process of hollow coaxial spinning in S2 is: the hollow structure formed by passing air into the inner layer is used as the inner layer, the mixed solution of regenerated cellulose fiber / PLA fiber is used as the middle layer, and the kenaf fiber solution is used as the outer layer for coaxial spinning, and the spinning voltage is 15-20kV. The mixture of regenerated cellulose fiber and PLA fiber provides elasticity and recovery, while the addition of kenaf fiber provides additional hardness and mechanical strength.
[0032] This combination helps maintain the loft and shape of the quilt core material and reduces deformation during use. The hollow structure of the regenerated cellulose fiber provides the basic loft and thermal insulation performance for the quilt core material. The elasticity and recovery of the polylactic acid fiber help maintain this fluffy structure and prevent fiber collapse or deformation during use. The toughness and wear resistance of the kenaf fiber provide additional structural stability for the hollow fiber and ensure the loft retention rate. The kenaf fiber as the outer layer provides additional hardness and mechanical strength, while the mixture of regenerated cellulose fiber and polylactic acid fiber provides elasticity and recovery. This structure helps maintain the shape and structure of the quilt core material and reduces deformation during use.
[0033] The elasticity of the middle layer of regenerated cellulose / polylactic acid fiber combined with the rigidity of the outer layer of kenaf fiber not only resists collapse caused by external pressure, but also ensures rapid recovery after compression, avoiding a decrease in fluffiness due to fiber fatigue. The hollow structure combined with the curled form further expands the gaps between fibers, significantly improving fluffiness; asymmetric cooling solidifies the special-shaped cross-section of the hollow fiber, enhances air retention capacity, and synergistically improves warmth retention. The three-layer structure with a soft inner layer, a supporting middle layer, and a stable outer layer allows the fiber to maintain high resilience and compression resistance after shaping, and maintain a fluffy state for a long time.
[0034] The spinning outlet cross-section in S2 is one of a triangle and an ellipse. When the spinning outlet cross-section is a triangle, the triangle is an isosceles triangle with a base-to-height ratio of 1.5-2.5:1, and the inner center of the triangular cross-section coincides with the axis of the regenerated cellulose / polylactic acid. The special-shaped cross-section increases the gaps between the fibers, thereby forming more air layers in the quilt material, and has a high elastic modulus, which can make the fiber more resilient than a circular cross-section. Hollow fibers are self-supporting, which means they can maintain their shape without the need for additional support, allowing the quilt material to remain fluffy after long-term use.
[0035] The kenaf fiber solution in the outer layer forms a fiber layer with high rigidity after solidification. This layer can enhance the overall structural strength of the fiber, making it more durable. The rigidity of the kenaf fiber can also restrain the outer and middle layers, preventing them from excessive deformation when subjected to external forces, thereby maintaining the shape and stability of the fiber. When the fiber is bent, the rigidity of the outer layer can resist bending deformation, while the flexibility of the inner and middle layers can absorb the bending stress, allowing the fiber to maintain both shape stability and certain elasticity when bent.
[0036] When the fiber is bent, the air chamber inside it is compressed and redistributed. Since the inner and middle layers have a certain degree of flexibility and elasticity, they can adapt well to this compression and redistribution, thereby maintaining the fiber's loft. The rigidity of the outer layer can prevent the fiber from excessive deformation and collapse when bent, further maintaining the fiber's loft and shape stability.
[0037] The asymmetric cooling method in S3 is to blow air on both sides of the hollow coaxial spinning fiber for cooling. The cooling temperature on one side is 5-10℃, the wind speed is 10-20m / s, and the cooling temperature on the other side is 25-30℃, and the wind speed is 3-5m / s. Asymmetric cooling can form a faster cooling speed on one side of the fiber, while the other side is relatively slow. This differential cooling helps to form a stable curling structure, thereby improving the fluffiness and elasticity of the fiber. The internal stress formed in the fiber is retained and converted into the asymmetric tension of the fiber, which is then amplified, so that each fiber forms a significant spiral curling effect. Asymmetric cooling can enhance the mechanical properties of the fiber, such as tensile strength and wear resistance, which helps the core material maintain its shape and structure after rebounding and reduce deformation.
[0038] The cooling temperature is 5-10℃, and the blowing side is facing the wide side of the triangular cross-section of the hollow coaxial spinning fiber. When the bottom edge is cooled, the contact area is larger, and the shrinkage stress distribution is more uniform, which can induce the fiber to bend toward the cooling side as a whole, forming a gentle arc curl. After cooling and solidification, it can serve as a support layer to prevent the hollow cavity from collapsing due to uneven shrinkage, thereby maintaining the fluffiness. Bottom edge cooling induces the fiber to form a large arc curl, the intersection points between fibers are reduced, and the porosity is increased; the porous arrangement of the hollow structure cavity and the special-shaped cross-section lengthens the heat conduction path, improving the warmth retention of the fiber.
[0039] The combing speed in S4 is 10-30m / min, the setting temperature is 120-150℃, and the setting time is 5-10min. Appropriate combing speed can effectively improve the combing degree of the fiber, reduce the entanglement between the fibers, make the fibers looser and more uniform, and thus improve the fluffiness of the quilt core material. The setting of the setting temperature and time can help the fiber maintain its shape and structure after cooling, and prevent the fluffiness from decreasing due to fiber fatigue during use. By controlling the parameters during the combing and setting process, the uniform distribution of the fibers in the quilt core material can be ensured, the formation of lumps and voids can be reduced, and the overall quality of the quilt core material can be improved. Appropriate setting temperature and time can improve the strength and durability of the fiber, making the quilt core material less likely to deform during use and maintaining good fluffiness.
[0040] In order to achieve the above-mentioned purpose, the second set of technical solutions adopted by the present invention is: a regenerated cellulose fiber quilt core material, which is prepared based on a regenerated cellulose fiber quilt core material and a preparation method thereof.
[0041] Embodiment 1
[0042] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0043] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 4:6. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle with a base to height ratio of 1.5:1, thereby obtaining a hollow coaxial spun fiber.
[0044] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0045] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0046] Embodiment 2
[0047] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0048] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 5:5. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle with a base to height ratio of 1.5:1, thereby obtaining a hollow coaxial spun fiber.
[0049] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0050] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0051] Embodiment 3
[0052] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0053] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 6:4. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle, and the ratio of the base to the height is 1.5:1, so as to obtain a hollow coaxial spun fiber.
[0054] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0055] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0056] Embodiment 4
[0057] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0058] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 7:3. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle with a base to height ratio of 1.5:1, thereby obtaining a hollow coaxial spun fiber.
[0059] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0060] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0061] Embodiment 5
[0062] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0063] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 8:2. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle with a base to height ratio of 1.5:1, thereby obtaining a hollow coaxial spun fiber.
[0064] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0065] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0066] Embodiment 6
[0067] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0068] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 6:4. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle with a base to height ratio of 1:1, thereby obtaining a hollow coaxial spun fiber.
[0069] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0070] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0071] Embodiment 7
[0072] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0073] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 6:4. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle with a base to height ratio of 2:1, thereby obtaining a hollow coaxial spun fiber.
[0074] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0075] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0076] Embodiment 8
[0077] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0078] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 6:4. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle, and the ratio of the base to the height is 2.5:1, so as to obtain a hollow coaxial spun fiber.
[0079] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0080] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0081] Embodiment 9
[0082] This embodiment prepares a regenerated cellulose fiber quilt core material, and the preparation method is as follows: S1: Dissolving regenerated cellulose fiber and polylactic acid fiber in a mass ratio of 7:3 to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution, wherein the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, and the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15%.
[0083] S2: The kenaf fiber is subjected to steam explosion pretreatment, and the steam explosion treatment process is as follows: the kenaf fiber is immersed in a 3% sodium hydroxide solution for 15 minutes, and after being taken out and dried, the kenaf fiber is placed in a steam explosion device for steam explosion treatment, and the air pressure in the steam explosion device is 2.5MPa, the steam explosion temperature is 60°C, and the pressure holding time is 6 minutes. The kenaf fiber pretreated by steam explosion is dissolved, and the kenaf fiber dissolution process is as follows: the kenaf fiber is placed in a vacuum drying oven at 70°C and dried for 12 hours, and then the dried kenaf fiber is immersed in an ionic liquid and stirred, and the stirring speed is 600rpm, and the stirring time is 2 hours to obtain a kenaf fiber solution, and the concentration of the kenaf fiber solution is 15%. The hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixture is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed. The spinning voltage is 20 kV, and the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution is 6:4. The spinning method used for the hollow coaxial spinning is coaxial electrospinning. The cross-section of the spinning outlet is an isosceles triangle with a base to height ratio of 3:1, thereby obtaining a hollow coaxial spun fiber.
[0084] S3: The hollow coaxial spun fibers in S2 are cooled by an asymmetric cooling method. The asymmetric cooling method is to cool the hollow coaxial spun fibers by blowing air on both sides. The cooling temperature on one side is 5°C and the wind speed is 15m / s. The cooling temperature on the other side is 30°C and the wind speed is 4m / s. Thus, cooled hollow coaxial spun fibers are obtained.
[0085] S4: The cooled hollow coaxial spun fibers in S3 are combed, laid and shaped respectively, with a combing speed of 20 m / min, a shaping temperature of 130° C. and a shaping time of 8 min to obtain a regenerated cellulose fiber quilt core material.
[0086] Comparative Example 1 This comparative example prepares a cotton fiber quilt core material, and the preparation method is as follows: Cotton fibers with a fineness of 8D were selected for carding, web laying and shaping, the carding speed was 20 m / min, the shaping temperature was 130° C., and the shaping time was 8 min, so as to obtain a cotton fiber quilt core material.
[0087] Test experiment: Take samples of equal mass from Examples 1 to 9 and Comparative Example 1, cover the samples on a block in a constant temperature and humidity environment of 25°C and 60%RH to ensure that the samples completely cover the block. The covering time is 500 hours, and test the sample thickness retention rate before and after covering and the thickness deviation rate after covering respectively. The thickness retention rate is the ratio of the average sample thickness to the sample thickness before constant temperature and humidity, and the thickness deviation rate is the standard deviation between several test points. The test results are shown in Table 1.
[0088] Table 1 Test data of thickness retention rate and thickness deviation rate of samples in Examples 1 to 9 and Comparative Example 1
[0089] It can be seen from Table 1 that the thickness retention rates of Examples 1 to 9 are all greater than those of Comparative Example 1, and the thickness deviation rates are all less than those of Comparative Example 1. The greater the thickness retention rate, the higher the fluffiness retention rate of the quilt core material, and the smaller the thickness deviation rate, the higher the uniformity of the quilt core material filling. The fluffiness retention rate and the uniformity of the quilt core material filling in Examples 1 to 9 are higher than those in Comparative Example 1. The preparation method of the regenerated cellulose fiber quilt core material in the present application has superiority.
[0090] In Examples 1 to 5, as the mass ratio between the regenerated cellulose fiber / polylactic acid fiber mixture and the kenaf fiber solution gradually increases, the thickness retention rate and thickness uniformity first increase and then decrease. This is because the high fiberization and mechanical properties of the regenerated cellulose / polylactic acid mixture dominate the fiber structure, forming a more stable hollow coaxial fiber skeleton. During the cooling process, the thermal shrinkage behavior of the regenerated cellulose / polylactic acid layer and the kenaf layer is significantly affected by the material ratio. The higher flexibility of the kenaf fiber can buffer the rigid shrinkage of the middle layer material and balance the stress distribution caused by the asymmetric cooling on both sides, thereby improving the thickness retention rate and uniformity; but when the mass ratio is too high, the coating capacity of the outer layer is insufficient, resulting in exposure of the middle layer or weakening of the interface bonding. During cooling, the difference in shrinkage between the inner and outer layers is aggravated, causing local stress concentration and structural deformation, which reduces the thickness retention rate and uniformity. The preferred embodiment is Example 3.
[0091] In the third embodiment and the sixth to ninth embodiments, as the ratio of the base to the height of the isosceles triangle of the spinning outlet cross section gradually increases, the thickness retention rate and the thickness uniformity first increase and then decrease. This is because when the base-to-height ratio increases moderately, the length of the base of the isosceles triangle outlet increases relatively, the lateral spreading of the spinning solution at the outlet is more sufficient, the symmetry of the liquid flow distribution is improved, the surface tension gradient in the initial stage of the jet is reduced, the uniformity of the fiber diameter is improved, the forming of the hollow inner layer is more stable, the hollow ratio of the fiber cross section is controllable, which is conducive to the uniform shrinkage in the subsequent cooling stage, the fiber structure is uniform as a whole, and the thickness retention rate and uniformity increase; when the base-to-height ratio is too high, the fiber cross section tends to be flattened, the difference in cooling rate on both sides directly acts on a larger surface area, causing local warping or curling, and the hollow structure is difficult to maintain due to excessive lateral extension. The inner and outer layers shrink uncoordinated during cooling, resulting in the initiation of microcracks inside the fiber, and the thickness retention rate and thickness uniformity decrease. The preferred embodiment is the seventh embodiment.
[0092] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a regenerated cellulose fiber quilt core material, characterized in that: The following steps are involved: S1: dissolving regenerated cellulose fiber and polylactic acid fiber to obtain a regenerated cellulose fiber / polylactic acid fiber mixed solution; S2: dissolving kenaf fibers to obtain a kenaf fiber solution, and hollow coaxially spinning the regenerated cellulose fiber / polylactic acid fiber mixed solution in S1 and the kenaf fiber solution to obtain hollow coaxial spun fibers; S3: Cooling the hollow coaxial spun fiber in S2 by an asymmetric cooling method to obtain a cooled hollow coaxial spun fiber; S4: combing, web laying and shaping the cooled hollow coaxial spun fibers in S3 to obtain a regenerated cellulose fiber quilt material.
2. The method for preparing a regenerated cellulose fiber quilt core material according to claim 1, characterized in that: The mass ratio of the regenerated cellulose fiber and the polylactic acid fiber in S1 is 6:4-8:2, the solvent in the regenerated cellulose fiber / polylactic acid fiber mixed solution is dimethyl sulfoxide, the total mass concentration of the regenerated cellulose fiber and the polylactic acid fiber in the regenerated cellulose fiber / polylactic acid fiber mixed solution is 15-20%, and the regenerated cellulose fiber is one of lyocell fiber, viscose fiber and modal fiber.
3. The method for preparing a regenerated cellulose fiber quilt core material according to claim 1, characterized in that: The kenaf fiber in S2 is pre-treated by steam explosion, and the steam explosion treatment process is: soaking the kenaf fiber in a 2-5% sodium hydroxide solution for 10-20 minutes, taking out and drying, and then placing the kenaf fiber in a steam explosion device for steam explosion treatment, the air pressure in the steam explosion device is 2-2.5MPa, the steam explosion temperature is 60-80°C, and the pressure holding time is 6-10min.
4. The method for preparing a regenerated cellulose fiber quilt core material according to claim 1, characterized in that: The kenaf fiber dissolution process in S2 is to place the kenaf fiber in a vacuum drying oven at 70° C. and dry it for 12 hours, then immerse the dried kenaf fiber in an ionic liquid and stir it at a stirring speed of 500-700 rpm for 2-3 hours, and the concentration of the obtained kenaf fiber solution is 10-15%.
5. The method for preparing a regenerated cellulose fiber quilt core material according to claim 1, characterized in that: The mass ratio of the regenerated cellulose fiber / polylactic acid fiber mixed solution to the kenaf fiber solution in S2 is 5:5-7:3, and the spinning method used in the hollow coaxial spinning is coaxial electrospinning.
6. The method for preparing a regenerated cellulose fiber quilt core material according to claim 5, characterized in that: The hollow coaxial spinning process in S2 is: the hollow structure formed by passing air into the inner layer is used as the inner layer, the regenerated cellulose fiber / polylactic acid fiber mixed solution is used as the middle layer, and the kenaf fiber solution is used as the outer layer, and coaxial spinning is performed at a spinning voltage of 15-20 kV.
7. The method for preparing a regenerated cellulose fiber quilt core material according to claim 1, characterized in that: The cross section of the spinning outlet in S2 is one of a triangle and an ellipse.
8. The method for preparing a regenerated cellulose fiber quilt core material according to claim 1, characterized in that: The asymmetric cooling method in S3 is to cool the hollow coaxial spinning fiber by blowing air on both sides, with the cooling temperature on one side being 5-10°C and the wind speed being 10-20m / s, and the cooling temperature on the other side being 25-30°C and the wind speed being 3-5m / s.
9. The method for preparing a regenerated cellulose fiber quilt core material according to claim 1, characterized in that: The combing speed in S4 is 10-30 m / min, the setting temperature is 120-150° C., and the setting time is 5-10 min.
10. A regenerated cellulose fiber quilt core material, characterized in that: It is prepared based on a regenerated cellulose fiber quilt core material and a preparation method thereof according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for dissolving and processing regenerated hemp fibre by employing ionic liquid
CN101225551A
Preparation method of enteromorpha regenerated cellulose fibers
CN103590124A
Degradable environment-friendly flocculus material and preparation method thereof
CN104264365A
Method for preparing polylactic acid fiber through solution spinning
CN107761187A
Preparation process of three-dimensional curled hollow polyester staple fiber
CN114592246A
Cited By
Preparation of regenerated cellulose fiber based on one-step ionic liquid method for dissolving kenaf bast and application thereof
CN122522429A